Photocatalytic deaminative benzylation and alkylation of tetrahydroisoquinolines with N-alkylpyrydinium salts - Schönbauer, David; Sambiagio, Carlo; Noël, Timothy; Schnürch, Michael (Beilstein Journal of Organic Chemistry, 2020)
A ruthenium-catalyzed photoredox coupling of substituted N-aryltetrahydroisoquinolines (THIQs) and different bench-stable pyridinium salts was successfully developed to give fast access to 1-benzyl-THIQs. Furthermore, secondary alkyl and allyl groups were also successfully introduced via the same method. Additionally, the typically applied N-phenyl group in the THIQ substrate could be replaced by the cleavable p-methoxyphenyl (PMP) group and successful N-deprotection was demonstrated.
Keywords: C–H functionalization; C(sp3)–C(sp3) coupling; deaminative coupling; Katritzky salt; photoredox catalysis